I would like to know what the equation is for as series of infinite terms which are multiplied by the order of the terms: $$ \sum_{i=0}^{\infty} \sum_{j=0}^{\infty}(ij) a^ib^j $$ $a$ and $b$ are both fractions. Thanks to the answers provided on the question " Simple approximation to a series of infinite terms ", I assume that the this simplifies to: $$ \sum_{i=0}^{\infty} ia^i \cdot \sum_{j=0}^{\infty}jb^j $$ A simple formula similar to the answers provided in the previous question would be much appreciated.


Assuming that $a$ and $b$ are constants with an absolute value less than 1.

Looking at each summation individually we know that from the Neumann series

$\displaystyle \sum_{i = 0}^{\infty} a^i = \dfrac{1}{1-a} $

Assuming that the derivative of the above series can be portrayed as

$\displaystyle f'(a) = \sum_{i = 0}^{\infty} ia^{i-1} = \dfrac{1}{(1-a)^2} $

After multiplying by $a$ on each side we get

$af'(a) = \displaystyle \sum_{i = 0}^{\infty} ia^i = \dfrac{a}{(1-a)^2}$

We can do the same with

$bf'(b) = \displaystyle \sum_{j = 0}^{\infty} jb^j = \dfrac{b}{(1-b)^2}$


$\displaystyle \sum_{i = 0}^{\infty} \sum_{j = 0}^{\infty} (ij)a^ib^j = \dfrac{ab}{(1-a)^2(1-b)^2}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.